Analysis of The Relationship Between Knowledge, Attitudes and Care of Perineal Wounds And Healing of Perineal Wounds In BPM Juliani - Ida Lestari Tampubolon (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Lacerations of the birth canal or episiotomy scarring require good wound care and care. If the treatment is not good then there canbe a puerperal infection due to microorganisms that attack laceration due to labor, whichis not a normal occupant of the cervix and birth canal. If the vulva and perineum are not clean, infection can easily occur in the perineal suture. The purpose of this study was to determine the relationship between knowledge of attitudes and treatment of perineal wounds in puerperal mothers with healing of perineal wounds at the BPM Juliani. This type of research used in this study is an analytical survey research method, with a cross sectional approach, while the population in this study is all post partum mothers in the BPM Juliani as many as 32 people. Wheresamples are takenusing total sampling techniques. Based on the results of the study using the chi-square test with α = 0.05 with a confidence level of 95%, witht heresults of this research knowledge 0.015, attitude 0.019, wound care 0.002, it can be seen the value of ρ = 0.001 <α = 0.005 where the value of ρ is smaller than α which means there is a relationship. The conclusion in this study is that there is a relationship between know ledge of attitude and treatment of perineal wounds in puerperal mothers with healing of perineal wounds at the BPM Juliani.